Electrical signaling, gas exchange and turgor pressure in ABA-deficient tomato (cv. Micro-Tom) under drought - Macedo, Francynês da Conceição Oliveira (2015)
This document refers to research whose main objective was to investigate the relationship among hydraulic, chemical and electrical signals in poor tomato plants ABA production. The document is organized into three chapters: The first chapter presents a detailed extracellular measurement protocol of electrical signals in plants and how to associate these measurements to determine gas exchange using the Infrared gas analyzer (IRGA) and turgor pressure using the patch clamp pressure probe (ZIM-probe). The second chapter refers to recording of the action potential generated spontaneously and evoked by electrical stimulation in ABA-deficient tomato, mutant sitiens. The final chapter presents the results for turgor pressure, gas exchange and electrical signals measurements in mutants notabilis and sitiens in the re-irrigated after a period of drought. The possible role of electrical signals in the plant signalling under stress conditions is discussed. The main conclusions related to chapters 1, 2 and 3 were: Measurement of extracellular electrical signals can be performed with gas exchange and turgor pressure measurements using IRGA ZIM-probe equipment; Electrical signals generated spontaneously in sitiens mutants propagate with amplitude and speed higher than in wild plants. Mutant is less responsive to electrical stimulation showing higher excitation threshold and longer refractory period than wild plants; The mutant plants are more responsive electrically to re-irrigation after drought than wild plants. The electrical signals precede changes in gas exchange in all genotypes, post irrigation. The ZIM-probe was not efficient to evaluate the turgor pressure in mutant plants under stress conditions, but is a promising tool for studies involving hydraulic and electrical signalling in wild plants.